Effect of solar radiation to the building materials properties: a review / Raihana Mohamad Hata …[et al.] - Mohamad Hata, Raihana; Hassan, Rohana; Arshad, Fadzil; Idayu, Haslin (Universiti Teknologi MARA Shah Alam, 2016)
This paper provides a review on the effect of solar radiation to the different building materials properties. Solar radiation; watt per meter square [W/ m2] is one of the cause for thermal gain in building envelopes. Buildings envelopes comprises of various materials. Different materials have different rate of heat absorption depends on their emissivity and other parameters. The three materials studied in this paper are concrete, timber and composites materials. According to the radiation heat equation, heat rate are affected by the surface area of exposed envelope (A) measure in meter (m), emissivity of the building exposed surface (ε) and the temperature difference between envelope exposed surface (Ts) and temperature of equivalent atmosphere (Tsky) measure in 0C. Based on the parameters, research methodology was adopted either by software simulation or test field experimental. Solar radiation affects the materials in various ways, depends on parameters considered, location of testing and type of materials.